Study on shear connection of bridge steel truss and concrete slab deck. Issue 1 (2nd January 2017) - Machacek, Josef; Charvat, Martin
Abstract: Longitudinal shear flow in the connection of a bridge steel truss upper chord and a concrete bridge slab is studied both in elastic and plastic stages of loading up to the shear connection collapse. First the distribution of the shear flow with an increasing level of loading is shown as resulted from 3D MNA (materially nonlinear analysis) using ANSYS software package and a former experimental verification. Nevertheless, the flow peaks in elastic stages above truss nodes due to local transfer of forces are crucial for design of the shear connection in bridges. Therefore a simple approximate 2D elastic frame modelling was suggested for subsequent extensive parametric studies. The study covers various loadings including the design loading of bridges and demonstrates importance of rigidity of the shear connection, rigidity of an upper steel truss chord and rigidity of a concrete deck. Temperature effects and a creep of concrete are also studied. The substantial part of the study deals also with concentration of shear connectors in the area of steel truss nodes and influence of the connector densification on distribution of the longitudinal shear along an interface of the steel truss chord and the concrete deck. Eurocode 4 approach and quest to find an optimum design of the shear connection in composite bridge trusses are discussed. Finally the resulting recommendations for a practical design are presented.